Assessment of cognitive asymmetries in brain-damaged and normal subjects: validation of a test battery. Issue 8 (August 1979) - Bentin, S; Gordon, H W
Abstract : A test battery designed to assess cognitive functions normally related to the left and right cerebral hemispheres was validated on 30 patients with unilateral (16 right, 14 left) lesions. The tests were preselected to reflect typical functioning of the hemispheres according to general agreement in the literature. A Cognitive Laterality Quotient (CLQ) was calculated from the difference in performance between the "right" and "left" test batteries and, therefore, reflected the relative functioning attributed to the right and left hemispheres. Using the CLQ measurement and a control group of 30 non-neurological patients matched for age and education, 28 out of 30 brain-damaged patients (93%) were categorised correctly according to side of lesion; the other two were considered to have either abnormal lateralisation (one was left handed) or asymmetrical premorbid cognitive profiles. Using only one (paired) test whose two subparts were designed to vary only slightly in task requirements to measure either right or left functioning, 29 out of 30 patients were correctly categorised. It is suggested that the concept of relative assessment of basic cognitive functions is more fruitful than general assessment of intellectual functions for use in diagnosis and rehabilitation of neurological patients or normal subjects with developmental or acquired behavioural cognitive abnormalities.